Incorporating amenity and ecological values of urban water into planning frameworks: evidence from Melbourne, Australia. Issue 1 (2nd January 2017) - Cooper, Bethany; Crase, Lin; Maybery, Darryl
ABSTRACT: Australia is one of the most urbanised nations on Earth with 89 per cent of the population currently classified as living in urban areas (United Nations 2014, World urbanisation prospects, 2014 revision, United Nations, New York). This concentration of human populations in metropolitan centres puts added pressure on natural landscapes that remain within city boundaries, like urban waterways. Successful management of these 'natural' assets requires an understanding of their wider contribution to human well-being, including the psychological gains from access to nature. Whilst the benefits of 'blue space' in urban environments have recently attracted attention in Europe (e.g. Völker, S & Kistemann, T 2011, 'The impact of blue space on human health and well-being – Salutogenetic health effects of inland surface waters: a review', International Journal of Hygiene and Environmental Health, vol. 214, no. 6, pp. 449–460), there is relatively little formal literature dealing with the benefits of urban waterways in Australia. In addition, many of the conceptual frameworks for contemplating these benefits do not easily lend themselves to formulating practical advice for waterway managers, with many important values aggregated. This article sets out a systematic way to conceptualise and measure the contribution of urban waterways to human well-being. Whilst simplified in some ways, the proposed method offers managers a practical tool for encapsulating benefits into economic measurement techniques. The framework has the advantage of providing a vehicle for ensuring important values are not overlooked as part of the planning process.